2020
DOI: 10.1002/aic.17115
|View full text |Cite
|
Sign up to set email alerts
|

Product tri‐section based crude distillation unit model for refinery production planning and refinery optimization

Abstract: Accuracy of a crude distillation unit (CDU) model has a significant impact on refinery production planning. High accuracy is typically accomplished via nonlinear models which causes convergence difficulties when the entire refinery model is optimized. CDU model presented in this work is a mixed‐integer linear model with a modest number of binary variables; its accuracy is on par with rigorous tray to tray CDU models. The model relies on the observation12 that a line through the middle of the product true boili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The CDU model described by Fupei Li et al is a mixedinteger linear model incorporating a reasonable amount of binary variables. Its accuracy is comparable to more comprehensive trayto-tray CDU models [3]. In their study, Bayomie et al provide an algorithm designed to address the energy recovery challenges faced by contemporary refiners.…”
Section: Modelling Of Crude Distillation Unitmentioning
confidence: 99%
“…The CDU model described by Fupei Li et al is a mixedinteger linear model incorporating a reasonable amount of binary variables. Its accuracy is comparable to more comprehensive trayto-tray CDU models [3]. In their study, Bayomie et al provide an algorithm designed to address the energy recovery challenges faced by contemporary refiners.…”
Section: Modelling Of Crude Distillation Unitmentioning
confidence: 99%
“…Thus, the overall economic performance evaluation of the refinery is directly influenced by the proper simulation of CDU operation [8,10]. Different models of CDU operation simulation have been reported in the literature [7,[11][12][13]. However, our search of the literature has shown that the CDU operation simulation has not considered the deviation of distillation yields from crude oil blends from the additive blending rule, as reported in the research of Li et al [14,15], when crude oil blends are processed.…”
Section: Introductionmentioning
confidence: 99%
“…They employed an optimality‐based interval reduction (OIR) technique to accelerate the branch‐and‐bound procedure of state‐of‐the‐art global solvers. Li et al 6 solved a mixed‐integer, nonlinear refinery planning problem featuring a novel product tri‐section CDU process model.…”
Section: Introductionmentioning
confidence: 99%